Melodies and maladies: reflections on Shakespeare and his portrayal of disease and death - Chatterjee, Pranab; Seth, Bhavna (Research and Humanities in Medical Education, 2014)
Shakespeare has long been acknowledged to be a pioneer in understanding the functions and dysfunctions of the human mind. However, very little discussion has centered on his knowledge of the physical science of medicine. In this article the authors reflect on Shakespeare’s portrayal of diseases and death in his work and conclude that he had significant knowledge of the contemporary medical sciences.